Simulation and modeling methodologies, technologies and applications : International Conference, SIMULTECH 2016, Lisbon, Portugal, July 29-31, 2016, revised selected papers /: International Conference, SIMULTECH 2016, Lisbon, Portugal, July 29-31, 2016, revised selected papers. ([2018]) - Unknown
No abstract available